Inner Architecture of Bonded Splats under Combined High Pressure and Shear. Issue 4 (14th December 2015) - Khoddam, Shahin; Sapanathan, Thaneshan; Zahiri, Saden; Hodgson, Peter D.; Zarei‐Hanzaki, Abbas; Ibrahim, Raafat
Abstract : Micron size aluminum particles (Figure 1) are deformed into "interlocked splats" at room temperature under high pressure and shear . Sample's induced inner architecture is examined (Figure 2). Tests are carried out to characterize material's heterogeneous properties (Figure 3). Presented formulation of the test data indicates an excellent shear strength; stronger than its solid counterpart.